Scientific Opinion on the substantiation of a health claim related to “Appl”In® polyphenolic apple extract powder (Malus domestica)” and reduction of post‐prandial glycaemic responses pursuant to Article 13(5) of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA Journal, 2011)
Abstract Following an application from Diana Naturals pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of France, the Panel on Dietetic Products, Nutrition and Allergies was asked to deliver an opinion on the scientific substantiation of a health claim related to “Appl”In® polyphenolic apple extract powder (Malus domestica)” and reduction of post‐prandial glycaemic responses. The food constituent, Appl'In® polyphenolic apple extract powder (Malus domestica Borkh.) containing at least 5 % phloridzin, is considered to be sufficiently characterised in relation to the claimed effect. The Panel considers that reduction of post prandial glycaemic responses (as long as post‐prandial insulinaemic responses are not disproportionally increased) may be a beneficial physiological effect. The applicant provided one published and two unpublished human studies, three animal studies and two in vitro studies as pertinent to the claim. The Panel notes that the food used in one human study did not comply with the specifications of the food which is the subject of the claim and considers that no conclusion can be drawn from this study for the scientific substantiation of the claim. In two other human studies, post‐prandial blood glucose concentrations were measured but not insulin responses. The Panel considers that no conclusions can be drawn from these studies for the scientific substantiation of the claim. The Panel concludes that a cause and effect relationship has not been established between the consumption of Appl'In® and reduction of post‐prandial glycaemic responses.